ANALISIS MEMBANGUN KETERLIBATAN DAN KOMUNIKASI GEN Z DENGAN KECERDASAN BUATAN DI PENDIDIKAN TINGGI - Rochmah, Tengku Sitti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Technological transformation requires lecturers to increase creativity and innovation in learning methods that can increase student engagement and communication skills which are currently being played by Gen Z who are very close to technology. Therefore an approach with artificial intelligence is one of the keys to success in increasing engagement and communication with Gen Z. The purpose of this research is to find out the involvement and communication of students with artificial intelligence in higher education. The research methodology uses descriptive qualitative descriptive methods with data collection techniques using journals, reports, books, and field observations. The results of the study show that the learning process with high student involvement needs to be developed by lecturers so that learning becomes interesting and easily understood by students and artificial intelligence technology in higher education can be a creative learning innovation with student involvement and communication skills in responding to students living in today's digital era.